POTENSI VEGETASI PADA EMBUNG DI DESA BANFANU KABUPATEN TIMOR TEGAH UTARA SEBAGAI PENDUKUNG KETERSEDIAAN DAN KONSERVASI AIR - Remigius Binsasi; Yolanda Getrudis Naisumu; Maria Anfrida Bano (BIO-EDU: Jurnal Pendidikan Biologi, 2022)
Nowdays, the necesity of the water go up on every sectors, so that it caused the water go down because of the management is not good enough. The purpose of this study is to know the kinds of the vegetation that found in the haze, that can be benefit to suport the water availibility and conservation, to know the potency of the vegetacy as the water availibility and conservation an also to know the society role to support it. This study is started from December 2020 until March 2021 placed in haze Banfanu village, North Central Timor regency. This study is used the qualitative and quantitave method. To collect the data and analysing the writer used an interview, observation and documentation. The determination estimasy data analysing is used point center quarter method (PCQM) to count point index value (PIV), the variety index shanon winner and averrage index. This study is made on twelve simpling with the vegetation data that is pick out from the tree, pilar and seedling. The result of this study is indicated that there are 28 species in the haze at the Banfanu village that consist of 16 families from 404 individu is devided in seedling, pilar and tree. The vegetation that could be benefit the water availibility and concervation is Switenia mahagoni, Casuarina junghuniana, Syzygum aqueum, Bambusa vulgaris, Ficus benjamina, Pandanus dubius Spreng, Paraserianthes falcataria (L) Nielsen, Anacardium occidentae L, Psidium Guajava L, Timonius sericeus (Deft) K. Schum, Syzygium cimunu L. The vegetation that indicate to keep up the water avalibility concervation is Bambusa vulgaris, the vicus kind is switenia mahogani, and iti is supported by the data analysis is higher index point value to tree strata is tectona grandis with IPV 74.50% and the lower IPV is Musa paradisiaca with IPV 1.80%. The higher point value for the pilar is Gliricidia sepium with IPV 92.13% and the lower is Vachellia leucophloea with IPV 2.99%, the high IPV for seedling is Tectona grandis with IPV 46.80% and the lower is switenia mahogani L and Sesbiana grandiflora with IPV 0.90%. The variety index value Shanon Winner and the averrage index categorize is lower. The vegetacy kind in the haze of Banfanu village categorize lower variety vegetacy, bad productivities, the condition is not rateable and lower pressure, but the ratebale index happend because of the domination on the kind certain species and in generally the kind of plant that growth up is limited. In other hand, the knowledge of the society is not enough to keep the water availibility and concervation and also the vegetacy is a polemic to the society.